A mathematical modeling approach to university course planning. (June 2022) - Khamechian, Mohammad; Petering, Matthew E.H.
Highlights: We introduce two new optimization problems related to university course planning. The first problem is called the student course planning problem (SCPP). The second problem is called the department course planning problem (DCPP). The objective is to minimize the time needed to complete a university degree. Three proposed math models provide swift insight into university degree programs. Abstract: This study introduces two optimization problems related to university course planning. In the student course planning problem (SCPP), a student needs to design a course plan that allows him/her to graduate in a timely manner. In the department course planning problem (DCPP), an academic department needs to decide which courses to offer during which semester to facilitate students' timely graduation. Mathematical models of these problems are developed, coded in C++, and solved with IBM ILOG CPLEX. Experiments on small, medium, and large real-world and fictional instances show promising results.